Guiding the guides: Strengthening teachers’ group counseling skills in an Islamic boarding school - Yuli Rahmawati; Fatiya Halum Husna; Ridwan Aji Budi Prasetyo; Miranti Alifia (University of Merdeka Malang, 2026)
Teachers in Islamic boarding school settings, such as SMPI Sabilurrosyad, face complex challenges in addressing students’ academic and psychosocial needs. In addition to supporting students’ achievement in formal and Islamic subjects, teachers are also responsible for cultivating moral character. Group counseling is an important competency that enables teachers to support students in dealing with developmental, emotional, academic, and social concerns. This community service program aimed to strengthen teachers’ understanding and ability to apply basic group counseling skills. The program was implemented through structured counseling training that covered key concepts of group counseling, its stages, and practical role-play activities. Teachers actively participated in experiential learning sessions designed to build confidence and readiness to apply counseling skills in the school context. The findings indicate an improvement in teachers’ counseling self-efficacy, although the change was not statistically significant. Participants’ reflections showed that the training helped clarify the group counseling process and increased their confidence in applying these skills to support students. This community service program contributes to strengthening counseling literacy among teachers and offers a potential model for sustainable group counseling capacity building in Islamic boarding school-based educational institutions.